The Harlem Hellfighters : when pride met courage - Myers, Walter Dean, 1937- (HarperCollins, 2006)
Tells the story of the 369th Infantry, an African American regiment that risked their lives for the country they loved during World War I and emerged triumphant, in spite of the bigots and racists who did everything possible to make them fail.